2010
DOI: 10.1111/j.1439-0426.2010.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein and lipid levels on growth and feed utilization of wild-caught striped sea bream, Lithognathus mormyrus

Abstract: A feeding trial was carried out to determine the effects of dietary protein and lipid levels on the growth performance and feed utilization of wild-caught striped sea bream (Lithognathus mormyrus). The experimental fish were collected from a local lagoon (Ç ardak Lagoon, Ç anakkale, Turkey), transferred to the Marine Net Cage Unit and fed by hand to apparent satiation with a commercial sea bream feed (Biomar; 42% crude protein, 16% crude lipid). Approximately 4 weeks were needed to acclimate the fish to farmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, the optimal dietary protein levels found for other sparid species have been reported to be around 50% [13] and [14]. In a recent study, Kusku et al [15] indicated that stripped seabream (Lithograthus mormyrus) can be easily adapted to farming condition in net cages and that a diet containing 50% crude protein and 15% crude lipid levels with 23g protein MJ -1 gross energy of protein/energy ratio would be suitable for stripped seabream growth. Thus, the protein (47.17-48.80%), lipid (13.80-14.09%) and P:E ratio (22.14-23.42) found in commercial diets in the present study could be considered optimum for sobaity.…”
Section: Discussionmentioning
confidence: 96%
“…However, the optimal dietary protein levels found for other sparid species have been reported to be around 50% [13] and [14]. In a recent study, Kusku et al [15] indicated that stripped seabream (Lithograthus mormyrus) can be easily adapted to farming condition in net cages and that a diet containing 50% crude protein and 15% crude lipid levels with 23g protein MJ -1 gross energy of protein/energy ratio would be suitable for stripped seabream growth. Thus, the protein (47.17-48.80%), lipid (13.80-14.09%) and P:E ratio (22.14-23.42) found in commercial diets in the present study could be considered optimum for sobaity.…”
Section: Discussionmentioning
confidence: 96%
“…It is important to ideal for both costeffective and eco-friendly reasons; the level of protein and amino acid in aquafeeds must be balanced because dietary protein sources are expensive (Li, Mai, Trushenski & Wu, 2009;Wilson, 2002). The optimum protein and amino acid requirement for maximum fish performance differ depending on the species, size of fish, rearing conditions, environmental factors, dietary energy and quality of the dietary proteins (Abdel-Tawwab, Ahmad, Khattab & Shalaby, 2010;Bechara, Roux, Ruiz Diaz, Flores Quintana & de Meabe, 2005;Castro et al, 2012;El-Sayed, Mansour & Ezzat, 2003;Henry & Fountoulaki, 2014;Kusku et al, 2011;Liu, Mai, Liufu & Ai, 2014;Oz orio et al, 2009;de la Serrana et al, 2013;Skalli, Hidalgo, Abell an, Arizcun & Cardenete, 2004).…”
mentioning
confidence: 99%
“…The effects of dietary lipid levels on growth performance and nutrient utilization depend on fish species, fish size, dietary protein-to-lipid ratio, or capability of fish to use carbohydrates as an energy source, dietary protein and energy levels and feeding time (Sargent et al, 2002;Kusku et al, 2011 (Metailler et al, 1981). The supplementation of dietary Ulva meal resulted in greater benefits when fed with higher-lipid diets.…”
Section: Discussionmentioning
confidence: 99%